Cultural desire need not improve with cultural knowledge: A cross-sectional study of student nurses. (July 2016) - Isaacs, Anton Neville; Raymond, Anita; Jacob, Elisabeth; Jones, Janet; McGrail, Matthew; Drysdale, Marlene
Abstract: Cultural desire is considered to be a prerequisite for developing cultural competence. This study explored cultural desire among student nurses towards Aboriginal peoples and its association with participation in a one-semester unit on Aboriginal health through a cross-sectional survey. Our main outcome, cultural desire, was measured using two items level of agreement with Aboriginal health being an integral component of the nursing curriculum and an expressed interest in Aboriginal health. 220 (74.58%) student nurses completed the survey. Completing the Aboriginal Health and wellbeing unit did not influence students' opinions on inclusion of the unit as part of the nursing curriculum (odds ratio OR 0.73, 95% CI 0.43–1.29) or their overall cultural desire (mean difference = −0.69, 95% CI −1.29 to −0.08, p = 0.026). Students who completed the unit reported a higher understanding of Aboriginal health (OR = 2.35, 95% CI = 1.35–4.08) but lower interest levels in the subject (OR = 0.45, 95% CI: 0.24–0.84). Further research is necessary to explore how and when cultural desire might develop in nurses who are trained in cultural competence particularly in the contexts of post-colonial disparities and political conflict.